Pengembangan Media Pembelajaran Wayang pada Materi Hubungan Antar Mahkluk Hidup dalam Ekosistem Terhadap Kemampuan Literasi Sains Siswa Kelas V - Rahayu, Nur Salsabila; Andriana, Encep; Hendracipta, Nana (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This research aims to develop learning media in the form of wayang. The development of this learning media uses the Research & Development (R&D) method. The resulting media is wayang learning media for scientific literacy skills. This research was conducted at SDN Renged 3 with 35 class V students as research subjects. Researchers use a research approach that refers to the ADDIE development model. The results of the development of wayang learning media on the scientific literacy abilities of class V students at SDN Renged 3 show that wayang learning media is included in the "very feasible" category. This can be seen from the validation results with validator lecturers, the average percentage value is 86% and the results of student responses average value 85%. The results of the scientific literacy ability test for class V students at SDN Renged 3 showed a pretest score of 38%, the "not good" category became a posttest score of 51%, the "fairly good" category after using wayang learning media with an increase of 0.22 was "low".